Salivary Biomarker Levels in Children with Sleep Problems Before and After Twin Block Therapy - Trupti Balasaheb Bhosale; Vabitha Shetty (Wolters Kluwer Medknow Publications, 2024)
Background: Disturbances in sleep have a wide-ranging effect on a child's life profoundly impacting the standard of living. The aim of this study was to investigate levels of Salivary Tumor Necrosis Factor-Alpha (TNF-α) and Malondialdehyde (MDA) in a group of children with class II malocclusion and sleep problems before and after twin block appliance therapy. Materials and Methods: Eleven children aged 8-12 years with skeletal class II malocclusion and at least one sleep disorder participated in the study. All children were subjected to a recording of their sleep history and a clinical and radiographic examination. Pre-treatment levels of salivary TNF-α and MDA were recorded. A twin block appliance was custom made and delivered to every child. After a minimum follow-up period of 9 months, all children were recalled for a re-evaluation of salivary biomarker levels. Results: Levels of salivary biomarkers TNF-α and MDA significantly decreased in children following myofunctional therapy using a twin block appliance. Conclusion: The measurement of TNF-α and MDA could be used as an alternative and noninvasive method to evaluate prognosis of twin block therapy for children with sleep-disordered breathing (SDB).